Plant-derived extracellular vesicles as a novel tumor-targeting delivery system for cancer treatment - Wu, Hanjin; Shi, Mengya; Meng, Liwei; Qiu, Jie; Jiang, Yuancong; Qian, Da; Shen, Fengqing (Frontiers in Cell and Developmental Biology, 2025)
Extracellular vesicles (EVs) are vital mediators of intercellular communication, helping to transfer bioactive molecules to target cells and demonstrating significant potential in antitumor therapy. Currently, EVs are primarily utilized in clinical applications such as biomarker discovery, cell-free therapeutic agents, drug delivery systems, pharmacokinetic studies, and cancer vaccines. Plant-derived EVs (P-EVs) contain a range of lipids, proteins, nucleic acids, and other metabolite cargos, and it is possible to extract them from various plant tissues, including juice, flesh, and roots. These vesicles perform multiple biological functions, including modulating cellular restructuring, enhancing plant immunity, and defending against pathogens. P-EVs have also been investigated in various clinical trials due to their promising therapeutic properties. In the context of precision medicine, selectively inhibiting solid tumor growth while preserving the viability of normal human cells remains a primary objective of cancer therapy. However, the tumor microenvironment (TME) supports tumor progression through the facilitation of immune evasion, supplying nutrients, and promoting invasive growth, metastatic processes, and treatment resistance. Consequently, the development of novel antitumor agents is essential. Owing to their inherent therapeutic properties and potential as treatment vectors, natural P-EVs represent a promising biocompatible platform for targeted solid tumor therapy. These vesicles may contribute to remodeling the TME and enhancing antitumor immunity, offering innovative avenues for cancer treatment and improved human health.